Extended-range PMSM sensorless speed drive based on stochastic filtering. - Bolognani, S. (IEEE Transactions on power electronics)
The paper describes the design of a high-performance sensorless permanent magnet synchronous motor (PMSM) drive, capable of starting at full torque even from standstill and able to deliver full torque in 1:12 speed range. Experimental setup, hardware circuitry and software implementation are described into details. Particular emphasis is given to the software control algorithms, that were specifically studied to enhance the overall system performance